1975
DOI: 10.1002/pen.760150609
|View full text |Cite
|
Sign up to set email alerts
|

Studies of polyethylene shish‐kebab structures

Abstract: An experimental method initiated by Williamson and Busse has been extended to produce veil‐free shish kebab structures in linear polyethylene without need for severe recovery treatments. The technique involves the dilution of polymer in a concentrated solution of low molecular weight paraffin followed by a simple isothermal shear. The resulting shish kebab structures are isolated from the wax matrix and subjected to electron microscopical and electron diffraction study. From the diffraction patterns, it is sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1976
1976
2006
2006

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…George and Tuc ker [12] hav e measured th e mean diam eter a s of the fibrils that we re produced by mild s hear o[ a 3 1 /2 percent solution of polyeth ylene in n-octadecane at 84 O( and 101°C. They also measured th e mean di stance be twee n th e lamellar platelets at th ese two temperatures, whi ch we take to approximate th e characte ri stic length L s (table 1).…”
Section: Dependence Of Fibril Diameter and Characteristicmentioning
confidence: 99%
See 2 more Smart Citations
“…George and Tuc ker [12] hav e measured th e mean diam eter a s of the fibrils that we re produced by mild s hear o[ a 3 1 /2 percent solution of polyeth ylene in n-octadecane at 84 O( and 101°C. They also measured th e mean di stance be twee n th e lamellar platelets at th ese two temperatures, whi ch we take to approximate th e characte ri stic length L s (table 1).…”
Section: Dependence Of Fibril Diameter and Characteristicmentioning
confidence: 99%
“…An investigation of eq (1) where we may defin e a reduced free energy of formation function as (12) By simply taking dy / dn = 0 , it is found that n * = 2/3, corresponding to /lcf>* = 32a-2 a-el(/lJ)2, and it is seen by inspection of eq (11) that /lcf> = 0 when n = 1, giving a A crossover on the n coordinate at n c = 1 (see fig. 2B).…”
Section: Preliminary Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The affinity for the reaction between M and X provides a multiplying effect upon the entropy production associated with the overall formation of product B from reactant molecule A. The authors have noted previously (7) that the diluent in the systems which they have used and described in this paper for producing fibrous crystals in certain cases does seem to have an influence upon the morphology of the transformed product. Similar observation has been recorded for systems of the type studied by Pennings and Keller previously referred to.…”
Section: Fibrous Crystals and Non-equilibrium Thermodynamicsmentioning
confidence: 75%
“…It is our purpose to discuss certain fibrous crystallizations which we have recently reported (7) produced in a flow similar to that of Pennings wherein the deformation initially is a simple shear. In contrast to the work cited above as well as more recent work of McHugh and Schultz (8), we are concerned with a solvent fluid of moderately high viscosity, namely, the viscosity of a melt of a normal p a r f i n in the region of 100°C.…”
Section: Introductionmentioning
confidence: 99%